Annual variations in the Martian bow shock location as observed by the Mars Express mission. Issue 11 (21st November 2016) - Hall, B. E. S.; Lester, M.; Sánchez‐Cano, B.; Nichols, J. D.; Andrews, D. J.; Edberg, N. J. T.; Opgenoorth, H. J.; Fränz, M.; Holmström, M.; Ramstad, R.; Witasse, O.; Cartacci, M.; et al.
Abstract: The Martian bow shock distance has previously been shown to be anticorrelated with solar wind dynamic pressure but correlated with solar extreme ultraviolet (EUV) irradiance. Since both of these solar parameters reduce with the square of the distance from the Sun, and Mars' orbit about the Sun increases by ∼0.3 AU from perihelion to aphelion, it is not clear how the bow shock location will respond to variations in these solar parameters, if at all, throughout its orbit. In order to characterize such a response, we use more than 5 Martian years of Mars Express Analyser of Space Plasma and EneRgetic Atoms (ASPERA‐3) Electron Spectrometer measurements to automatically identify 11, 861 bow shock crossings. We have discovered that the bow shock distance as a function of solar longitude has a minimum of 2.39 R M around aphelion and proceeds to a maximum of 2.65 R M around perihelion, presenting an overall variation of ∼11% throughout the Martian orbit. We have verified previous findings that the bow shock in southern hemisphere is on average located farther away from Mars than in the northern hemisphere. However, this hemispherical asymmetry is small (total distance variation of ∼2.4%), and the same annual variations occur irrespective of the hemisphere. We have identified that the bow shock location is more sensitive to variations in the solar EUV irradiance than to solar wind dynamic pressure variations. We have proposed possible interaction mechanisms between the solar EUV flux and Martian plasma environment that could explain this annual variation in bow shock location. Key Points: Automatically identified bow shock crossings by Mars Express over 5 Martian years of data The bow shock distance at the terminator increases by 11% from near aphelion to near perihelion Functional forms produced for bow shock response to solar EUV and dynamic pressure